2007
DOI: 10.1016/j.mad.2007.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Familial genes in sporadic disease: Common variants of α-synuclein gene associate with Parkinson's disease

Abstract: Genetic variation of the alpha-synuclein gene (SNCA) is known to cause familial parkinsonism, however the role of SNCA variants in sporadic Parkinson's disease (PD) remains elusive. The present study identifies an association of common SNCA polymorphisms with disease susceptibility in a series of Irish PD patients. There is evidence for association with alternate regions, of protection and risk which may act independently/synergistically, within the promoter region (Rep1; OR: 0.59, 95% CI: 0.37-0.84) and the 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 19 publications
5
42
2
Order By: Relevance
“…This would suggest that REP1 and other promoter polymorphisms that modulate gene expression should also have an effect on age at onset, although the effect may not be as dramatic as gene multiplication and therefore more difficult to detect. One study has reported earlier disease onset in patients with the long REP1 allele (denoted 261 here) [Hadjigeorgiou et al, 2005], but others were unable to replicate [Maraganore et al, 2006;Ross et al, 2007;Winkler et al, 2007]. We did find evidence for association of REP1 with age at onset, although the effect was relatively small and marginally significant.…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations
“…This would suggest that REP1 and other promoter polymorphisms that modulate gene expression should also have an effect on age at onset, although the effect may not be as dramatic as gene multiplication and therefore more difficult to detect. One study has reported earlier disease onset in patients with the long REP1 allele (denoted 261 here) [Hadjigeorgiou et al, 2005], but others were unable to replicate [Maraganore et al, 2006;Ross et al, 2007;Winkler et al, 2007]. We did find evidence for association of REP1 with age at onset, although the effect was relatively small and marginally significant.…”
Section: Discussioncontrasting
confidence: 63%
“…Association of SNCA polymorphisms with common forms of PD, however, has been more difficult to establish, because their effect size on disease risk is much smaller than that of causative mutations, and also because of inherent confounders such as disease heterogeneity, which are more serious in association studies than in linkage studies. A large and growing body of evidence now points to polymorphisms in SNCA and its regulatory regions as being associated with susceptibility to common non-Mendelian forms of PD [Pals et al, 2004;Mellick et al, 2005;Mueller et al, 2005;Maraganore et al, 2006;Ross et al, 2007;Winkler et al, 2007]. The REP1 polymorphism, in particular, has a direct functional relevance to PD via its effect on gene expression [Chiba-Falek and Nussbaum, 2001;Chiba-Falek et al, 2003].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the PD susceptibility variants that have been identified thus far, the best validated have involved those located in the α-synuclein ( SNCA ) gene, which also contains several pathogenic mutations that are linked to familial PD, and in the microtubule-associated protein tau ( MAPT ) gene (Gasser et al, 2011). More specifically, associations with PD have been identified in both Caucasian and Asian populations at the 3′ and 5′ ends of the SNCA gene (Mizuta et al, 2006; Mueller et al, 2005; Pankratz et al, 2009; Ross et al, 2007; Satake et al, 2009; Simón-Sánchez et al, 2009; Winkler et al, 2007), while the H1 haplotype in MAPT is associated with PD in Caucasians, but not in Asians owing to the almost complete absence of the H2 haplotype in that group (Evans et al, 2004; Healy et al, 2004; Skipper et al, 2004; Tobin et al, 2008; Wider et al, 2010). …”
Section: Introductionmentioning
confidence: 99%